2011
DOI: 10.2486/indhealth.ms1237
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Markers in Exhaled Breath Condensate in Lung Fibroses Are Not Significantly Affected by Systemic Diseases

Abstract: Exhaled breath condensate (EBC) is assumed to reflect processes in the lungs, yet itis unknown whether oxidative stress markers in EBC are affected by systemic disorders (atherosclerosis, hypertension, diabetes) or whether lung diseases increase markers in plasma and urine. 8-isoprostane, 4-hydroxy-trans-2-nonenale (HNE) and malondialdehyde (MDA) were measured using liquid chromatography-electrospray ionization-mass spectrometry (LC-ESI-MS/MS) in EBC, plasma and urine in 82 patients (45 with asbestosis and hya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 16 publications
3
11
0
Order By: Relevance
“…58 A study performed in individuals with silicosis and other pulmonary diseases showed increased levels of MDA in silicosis, including correlation with radiological severity. 59 On the other hand, in coherence with the data from our present study, a recent study performed in workers exposed to silica from ceramics in Turkey showed increased serum MDA and decreased SOD levels associated with silica exposure (with and without silicosis) in comparison to the nonexposed controls. 60 These discordant results may be related to exposure factors such as particle size distribution, exposure intensity, and duration of exposure, as well as the duration and severity of the disease.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…58 A study performed in individuals with silicosis and other pulmonary diseases showed increased levels of MDA in silicosis, including correlation with radiological severity. 59 On the other hand, in coherence with the data from our present study, a recent study performed in workers exposed to silica from ceramics in Turkey showed increased serum MDA and decreased SOD levels associated with silica exposure (with and without silicosis) in comparison to the nonexposed controls. 60 These discordant results may be related to exposure factors such as particle size distribution, exposure intensity, and duration of exposure, as well as the duration and severity of the disease.…”
supporting
confidence: 92%
“…Besides an increased activity of SOD, glutathione peroxidase and catalase were also observed in coal workers with pneumoconiosis when compared to a control group 58 . A study performed in individuals with silicosis and other pulmonary diseases showed increased levels of MDA in silicosis, including correlation with radiological severity 59 . On the other hand, in coherence with the data from our present study, a recent study performed in workers exposed to silica from ceramics in Turkey showed increased serum MDA and decreased SOD levels associated with silica exposure (with and without silicosis) in comparison to the nonexposed controls 60 .…”
Section: Discussionmentioning
confidence: 90%
“…Further studies are needed to elucidate any possible relationships. The measurement of markers in EBC is not commonly used in the practice of occupational medicine; nevertheless the results support its utility as a noninvasive technique for exploring the pathophysiology of lung diseases due to asbestos 32) and silica 33) . EBC collection and analysis is not considered a standard method for the medical practice yet, however repeated findings in groups of different subjects with pneumoconiosis support its usefulness.…”
Section: Discussionmentioning
confidence: 89%
“…Another sample type to examine oxidative stress in the lungs of IPF patients is exhaled breath condensate which can be evaluated to obtain information on the lungs in situ and for a variety of respiratory diseases on a trial basis [26]. It was also reported that oxidative stress measurement with exhaled breath condensate was unaffected by systemic diseases [27]. However, like the report by Daniil et al [11], the above studies performed single measurement in each patient.…”
Section: Discussionmentioning
confidence: 93%